Penerapan Good Governance pada Pelayanan Administrasi Kependudukan di Desa Sukaharja Kecamatan Sindang Jaya Kabupaten Tangerang - Sefty Aryantika; Udin Syamsudin; Fitria Firdiyani (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
This thesis is entitled "Implementation of Good Governance in Population Administration Services in Sukaharja Village, Sindang Jaya District, Tangerang Regency". This study aims to determine the implementation of good governance in population administration services in Sukaharja Village, Sindang Jaya District, Tangerang Regency and the inhibiting factors in the implementation of good governance in population administration services in Sukaharja Village. This study uses a qualitative research method. The data collection techniques used are through observation, interviews, and documentation. The results of this study indicate that the implementation of the principles of good governance in Population Administration services in Sukaharja Village has been in accordance with the Principles of Participation, Transparency, Accountability, and Law Enforcement has been running well. Although in terms of effectiveness, there is still a lack of human resources which is a challenge in the implementation of good governance. The results of this study can contribute to the development of better village government policies and improve the quality of population administration services by improving human resources and training for village employees and developing a more effective information system. Thus, this study can help improve the effectiveness of population administration services in Sukaharja Village and contribute to the development of better village government.